2013
DOI: 10.13189/ujfns.2013.010102
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Growth of Cut-Flower Stock (Matthiola incana R. Br.) in Response to Differing in nutrient Level

Abstract: The present research project was aimed to study the effect of foliar application of zinc and NPK on growth of Stock (Matthiola incana.L. The study was carried out at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Application of phytohormones play a vital role in plant growth and productivity by comMunicating several signals among as well as inside the cells; but their internal level endures substantial variation under saline stress 5 , 17 , 18 . It has been revealed that salinity stress caused a decline in the production of plant growth regulators 19 , thus, foliage application of these growth regulators can even enhance their endogenous levels under salinity 20 , 21 . Triacontanol is a potential plant growth promoter and its foliar application has been reported to influence physiological and biochemical processes in plants under saline conditions 13 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Application of phytohormones play a vital role in plant growth and productivity by comMunicating several signals among as well as inside the cells; but their internal level endures substantial variation under saline stress 5 , 17 , 18 . It has been revealed that salinity stress caused a decline in the production of plant growth regulators 19 , thus, foliage application of these growth regulators can even enhance their endogenous levels under salinity 20 , 21 . Triacontanol is a potential plant growth promoter and its foliar application has been reported to influence physiological and biochemical processes in plants under saline conditions 13 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zinnia elegans treated with 1000 ppm potassium sulphate, nitrate, chloride, humate, and citrate yielded the tallest plants, particularly when potassium citrate and humate were used (Dorgham, 2019). The foliar application of larger doses of K and NP has improved their vegetative development and has increased the number of leaves on the plants (Sarwar et al, 2013). Increased meristematic activities is generated by potassium is linked to the increased leaf output (Verma and Verma, 2008).…”
Section: Plant Heightmentioning
confidence: 99%
“…It is an annual plant according to the region's conditions and perennial in other regions [1]. This plant is considered one of the important cut flowers and its flowers are of unlimited growth that shapes a star clusters with various colors including the red, yellow, purple, and violet and characterized with an odorous fragrance especially for the double-flowered species and therefore they are suitable for producing perfumes [2,3]. From a medical perspective, this plant is considered important as it is used to treat cancer and several dyes can be obtained from it like dark blue and purple.…”
Section: Introductionmentioning
confidence: 99%